PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP DISIPLIN KERJA PEGAWAI DI KANTOR KECAMATAN CIKARANG SELATAN - Sri Wahyuningsih; Yanti Noviah (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to determine the partial and simultaneous effect of work motivation and job satisfaction on employee work discipline at the South Cikarang District Office. The method used in this research is using quantitative research methods, the sampling used in this study is using the Nonprobability Sampling method and the type of sampling using saturated sampling. Total population of 40 respondents with a sample of 40 respondents. This study use multiple linear regression analysis to explain the effect of work motivation and job satisfaction on work discipline. The results of this study in terms of work motivation (X1) have a significant and partially positive effect on employee work discipline at the South Cikarang District Office. The job satisfaction variable (X2) has no partial effect on the work discipline of employees at the South Cikarang District Office. The variables of work motivation (X1) and job satisfaction (X2) have a positive and significant effect simultaneously on the work discipline of employees at the South Cikarang District Office. The influence of the independent variable on business work discipline is fifty-six point five percent.